2014
DOI: 10.1177/0194599814533494
|View full text |Cite
|
Sign up to set email alerts
|

Occult Primary Head and Neck Squamous Cell Carcinoma: Utility of Discovering Primary Lesions

Abstract: Objective Cancer of an unknown primary (CUP) squamous cell carcinoma metastatic to cervical lymph nodes is a challenging problem for the treating physician. Our aim is to determine if identification of the primary tumor is associated with improved oncologic outcomes and/or tumor characteristics including human papilloma virus (HPV) status. Study Design Retrospective, matched-pairs analysis contrasting 2 cohorts based upon discovery of primary lesion. Setting Tertiary teaching hospital. Subjects and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 20 publications
1
54
0
1
Order By: Relevance
“…In 1.5-9% of the cases, however, a primary tumour may not be identified, despite a systematic clinical work-up including tonsillectomy, random biopsies from the base of the tongue and nasopharynx, and magnetic resonance imaging of the head and neck (17). In such cases, the lymph node metastasis is defined as CUP of the head and neck region (10)(11)(12)(13)(14)(15)(16)(17). FNAC showing a cancer other than SCC, e.g.…”
Section: Cup Of the Head And Neck Regionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 1.5-9% of the cases, however, a primary tumour may not be identified, despite a systematic clinical work-up including tonsillectomy, random biopsies from the base of the tongue and nasopharynx, and magnetic resonance imaging of the head and neck (17). In such cases, the lymph node metastasis is defined as CUP of the head and neck region (10)(11)(12)(13)(14)(15)(16)(17). FNAC showing a cancer other than SCC, e.g.…”
Section: Cup Of the Head And Neck Regionmentioning
confidence: 99%
“…Recent studies reported the prevalence of HPV DNA, p16 or both in CUP of the head and neck region (10)(11)(12)(13)(14)(15)(16)(17). The highest HPV prevalence (59-92%) was observed in patients who were not subjected to tonsillectomy or random biopsies from the base of the tongue, who were at a higher risk of missing a minute TSCC or BOTSCC (17).…”
Section: Cup Of the Head And Neck Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…p16 IHC can be helpful to highlight small foci of SCC; but the expression must be strong and diffuse, as normal tonsillar crypt epithelium shows patchy p16 positivity. There is some evidence that identification of the primary site in a patient who initially presents with an unknown primary is associated with improved overall survival [29]. However, the improved survival may simply be because a primary site is more likely to be detected for HPV-related metastases that present as unknown primaries, and HPV-related SCC is known to have better outcomes than HPV-unrelated SCC.…”
Section: Squamous Cell Carcinoma Of Unknown Primary In the Era Of Hummentioning
confidence: 99%